Development of non-contact measurement system using infra-red sensor - Kamalulfaizin Mohd Suhut (Kulliyyah of Engineering, International Islamic University Malaysia, 2009)
This dissertation presents a design and development of a non-contact displacement measurement system which can be used for research projects such as in material science and biology. A simple infrared pair sensor is used in this project. The experiment is carried out to investigate the IR response where infrared sensor is set at various configurations. The data obtained from the infrared sensor measure is plotted and then the IR response is produced. Since the infrard response is nonlinear, a mathematical transfer function for the response is generated. Based on piecewiise lineariation function, an appropriate program is produced to convert the sensor output to the corresponding displacement measurement. The heart of this system is a PIC16F877 microcontroller which controls the overall operation.